The turnout eaudiobook A read with jenna pick. - Abbott, Megan (Penguin Audio, 2021)
"Impossible to put down, creepy and claustrophobic. It’s ‘Whatever Happened to Baby Jane’ in ballet shoes." —Stephen King Best Book of the Year NPR • Wall Street Journal • Boston Globe • Library Journal • CrimeReads • LitReactor • Air Mail Longlisted for the Joyce Carol Oates Prize A TODAY Show #ReadWithJenna Book Club Pick An Instant New York Times Bestseller New York Times bestselling and award-winning author Megan Abbott's exquisite and disquieting new novel, “dark and juicy and tinged with horror” ( The New York Times Books Review ), set against the hothouse of a family-run ballet studio. With their long necks and matching buns and pink tights, Dara and Marie Durant have been dancers since they can remember. Growing up, they were homeschooled and trained by their glamorous mother, founder of the Durant School of Dance. After their parents' death in a tragic accident nearly a dozen years ago, the sisters began running the school together, along with Charlie, Dara's husband and once their mother's prized student. Marie, warm and soft, teaches the younger students; Dara, with her precision, trains the older ones; and Charlie, sidelined from dancing after years of injuries, rules over the back office. Circling around one another, the three have perfected a dance, six days a week, that keeps the studio thriving. But when a suspicious accident occurs, just at the onset of the school's annual performance of The Nutcracker— a season of competition, anxiety, and exhilaration—an interloper arrives and threatens the sisters' delicate balance. Taut and unnerving, The Turnout is Megan Abbott at the height of her game. With uncanny insight and hypnotic writing, it is a sharp and strange dissection of family ties and sexuality, femininity and power, and a tale that is both alarming and irresistible.